Divorce, Abortion and Children's Sex Ratio: The Impact of Divorce Reform in China - Ang Sun; Yaohui Zhao (Institute for the Study of Labor (IZA), 2014)
This paper explores how the relative circumstances of men and women following marital dissolution affect sex-selection behavior within marriages. China's 2001 divorce reform liberalized divorce in favor of women and secured women's property rights after separation. We use this improvement in women's bargaining power in marriage for a regression discontinuity analysis of the demand for sex-selective abortions. We show that the increase in women's bargaining power reduces the propensity to have a son after a firstborn daughter by 8.9 percentage points. We also find that the effect is larger for women with higher health risks.
Keywords: D13; J12; J13; J16; 330; gender inequality; intra-household allocation; divorce law